2013
DOI: 10.7863/ultra.32.6.1003
|View full text |Cite
|
Sign up to set email alerts
|

Bedside Sonography for Detection of Postprocedure Pneumothorax

Abstract: Background Bedside ultrasonography in the diagnosis of pneumothorax has been well described in emergency and trauma medicine literature. Its role in detection of iatrogenic pneumothoraces has not been studied. We describe the performance of bedside ultrasonography in detection of procedure related pneumothoraces and highlight some limitations. Methods 185 patients underwent thoracentesis (n=60), transbronchial biopsy (n=48), CT-guided lung biopsy (n=76), and CT-guided cryoablation of a lung mass (n=1). Bedsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…Our results were also comparable to those found by Shostak E. et al [7] in a similar study but with minor procedures. They performed transthoracic ultrasound in a series of 185 patients submitted to thoracentesis, transbronchial biopsy and computed tomography-guided needle lung biopsy.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results were also comparable to those found by Shostak E. et al [7] in a similar study but with minor procedures. They performed transthoracic ultrasound in a series of 185 patients submitted to thoracentesis, transbronchial biopsy and computed tomography-guided needle lung biopsy.…”
Section: Discussionsupporting
confidence: 82%
“…However there is not such a consensus regarding ultrasound benefits in thoracic surgery patients. Different studies have been published proving bedside ultrasound is a valuable tool in the management of these patients [7] [10]- [16], meanwhile other authors have warned about the limitations of the technique [8] [17]- [20].…”
Section: Discussionmentioning
confidence: 99%
“…It is important, however, to mention that the high accuracy of ultrasonography has been evaluated predominantly among acute trauma patients [15] and not in a population of patients with underlying lung pathologies undergoing procedures with a potential for iatrogenic pneumothorax. Indeed, in the largest study which specifically examined this issue [16], it was shown that as much as a quarter of the studies were of limited quality due to lung and pleural pathologies, necessitating the use of chest X-ray. Furthermore, as of today, ultrasound technology and the knowledge required to utilize it is still not routinely available in all the centers performing bronchoscopy worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Literature: Guideline adaptation BTS 2010: Shostak et al [79], Sartori et al [74] de Novo Research: Garofalo et al [252], Kreuter et al [225], Kumar et al [226], Reissig and Kroegel [227] Consensus rate: 100%…”
Section: Evidence Gradementioning
confidence: 99%